A Preliminary Virtual Study on the Feasibility of Transferring Muscular Activation Pattern Behaviors of Psychomotor Exercises - Fabio Rossi; Álvaro González Mejía; Danilo Demarchi; Paolo Fiorini; Giovanni Gerardo Muscolo (Actuators, 2023)
Research has demonstrated that Taekwondo training helps to enhance the coordination capabilities in people with developmental coordination disorders. These excellent results depend on many factors, including the behavior of the muscular activation patterns of psychomotor exercises during Taekwondo training. Our basic idea is to study the behavior of the muscular activation pattern of Taekwondo training (performed by athletes) and to apply the adapted behavior of the muscular activation pattern to other subjects with reduced coordination capabilities to enhance them, in line with the sustainable human development goals. This paper presents a preliminary feasibility study and a first step in this direction using a virtual simulation. First, the Taekwondo front-kick exercise was studied and reproduced using a virtual human model in OpenSim. Second, some perturbations were applied to the virtual human model to analyze the behavior of the muscular activation patterns. Third, functional electrical stimulation (FES) patterns were properly simulated to reproduce the same sequence (and value) of signals of muscular activation in another subject. The proposed methodology was conceived on the basis of a simple example of a Taekwondo kick by using a virtual human model, but its general application can fit all kinds of psychomotor exercises. If future works confirm the simulation results presented in this paper with real implementation, the methodology proposed here could be applied every time human capabilities must be increased with or without sports training (e.g., remaining seated on a chair or lying on a bed).